2019
DOI: 10.4103/sajc.sajc_161_18
|View full text |Cite
|
Sign up to set email alerts
|

Influence of JAK2V617F allele burden on clinical phenotype of polycythemia vera patients: A study from India

Abstract: Background: Elevated JAK2V617F allele burden is associated with enhanced expression of downstream target genes in Philadelphia negative chronic myeloproliferative neoplasms (CMPNs) which include PV, ET & PMF. Previous studies have shown the impact of JAK2V617F … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 22 publications
(40 reference statements)
3
14
0
Order By: Relevance
“…10 14 However, our results are not in line with Sazawal et al in Indian population. 12 However, the rising trend in leukocyte count was observed, though not statistically significant as per study by Sazawal et al 12…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…10 14 However, our results are not in line with Sazawal et al in Indian population. 12 However, the rising trend in leukocyte count was observed, though not statistically significant as per study by Sazawal et al 12…”
Section: Discussionmentioning
confidence: 76%
“…Correlation of JAK2V617F with thrombosis and hematological parameters is documented in the literature with variable results. 9 10 11 12…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[19], [33]. These include prognostic variables such as haemoglobin concentration, white blood cell (WBC) counts, platelet counts and spleen size [26], [34] For instance higher V617F allele burden in PV patients corresponds to a pronounced myeloproliferative phenotype with increased haemoglobin levels [35]. Studies have revealed a direct correlation of JAK2V617F allele burden with activation parameters favouring thrombosis and associations of JAK2V617F allele burden with thrombotic risk [36], [37].…”
Section: Jak2 Allele Burden and Phenotypementioning
confidence: 99%
“…However, conventional risk factors are not PV-specific. In addition, only JAK2V617F variant allele frequency (VAF) > 50% has been associated with a higher thrombotic risk and bone marrow fibrosis in PV [ 11 , 12 ]. Aggressive hematocrit control <45% and use of cytoreductive treatment when required have been shown to reduce the number of thrombotic events and substantially improve survival [ 8 ].…”
Section: Introductionmentioning
confidence: 99%